2019
DOI: 10.14499/indonesianjpharm30iss3pp199
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Multiplate Resazurin Reduction Assay in The Screening for Anti-Mycobacterial Activity from Indonesian Medicinal Plants

Abstract: Tuberculosis (TB) is an airborne illness generated by Mycobacterium tuberculosis (Mtb), also one of the prominent infectious killers of adults worldwide. There is a pressing need to expand novel anti-mycobacterial drugs because of the increasing resistance of pathogenic mycobacteria to existing antibiotics. Native compounds acquired from microbial resources and medicinal cultivars have played an essential part as the origin of TB medications. The microplate resazurin reduction assay (MRRA) is generally utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recent studies have indicated that extracts of the bark, leaves, stem, pulp, and whole fruit of pomegranate have efective antimicrobial activity, including against multiresistant strains [29,30,71]. Moreover, they demonstrated the antibacterial activity of pomegranate against bacteria commonly involved in upper gastrointestinal tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have indicated that extracts of the bark, leaves, stem, pulp, and whole fruit of pomegranate have efective antimicrobial activity, including against multiresistant strains [29,30,71]. Moreover, they demonstrated the antibacterial activity of pomegranate against bacteria commonly involved in upper gastrointestinal tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…Each region has a distinctive plant utilization and is different from other regions. The utilization of different plants in each region is due to the diversity of plants in each region by Sari et al, [11]. One area that utilizes plants as medicinal materials by implementing an agroforestry system is the community living around the Bangkeng Buki' HKm located in Bukit Harapan Village, Gantarang District, Bulukumba Regency, South Sulawesi.…”
Section: Introductionmentioning
confidence: 99%
“…The strong colour of most extracts could obscure the judgment of the turbidity level and OD measurement (Ardalani et al, 2021;Liu et al, 2007). Recently, a fluorescence-based assay using oxidation-reduction indicator resazurin has been successfully implemented for high-throughput screening (HTS) of antibacterial agents (Kim & Jang, 2018;Sari et al, 2019;Teh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The strong colour of most extracts could obscure the judgment of the turbidity level and OD measurement (Ardalani et al, 2021; Liu et al, 2007). Recently, a fluorescence‐based assay using oxidation–reduction indicator resazurin has been successfully implemented for high‐throughput screening (HTS) of antibacterial agents (Kim & Jang, 2018; Sari et al, 2019; Teh et al, 2017). Resazurin (blue and not fluorescent) can be reduced by metabolically active cells to resorufin (pink and highly fluorescent) and upon further reduction to dihydroresorufin (colourless and not fluorescent).…”
Section: Introductionmentioning
confidence: 99%